Russian Federation’s FIMI prior to its Intervention in Ukraine - Yuskiv, Bohdan; Karpchuk, Nataliia P. (Routledge (New York), 2024)
“Foreign information manipulation and interference (FIMI)” is a pattern of behavior that threatens or has the potential to negatively impact values, procedures and policy processes. Destructive information activity of the Russian Federation in Ukraine and the world is an “illustrative case” of such behaviour. On the eve of the intervention in Ukraine on February 24, 2022, throughout 2021, the RF conducted a powerful special FIMI operation to promote the image of its extremely strong and invincible army. We claim that the goal of that FIMI was to intimidate the political elite of Ukraine and ordinary citizens, to eliminate any desire to fight as practically “suicidal”, to induce the state leadership and the President, in particular, to make decisions in favor of the RF. Since Ukrainians give great preference to various Telegram channels as a quick source of “insider” information, the paper scrutinises key messages about the RF army published in the state-owned Russian (RIA Novosti), a number of pro-Ukrainian and Ukrainian pro-Russian Telegram channels. The authors aim to prove that the publications regarding the image of the Russian army were a RF special FIMI operation. The paper contributes to further understanding of foreign information manipulation and interference as a growing political problem and a challenge to states’ national security
Keywords: foreign information manipulation and interference; special information operation; Telegram channel; Armed Forces